The New Grove Dictionary of Musical Instruments. Edited by Stanley Sadie. London: Macmillan Press: New York: Grove's Dictionary of Music, 1984. [Vol.I, xxvi, 805p; Vol.II, xiii, 982p; Vol.HI, xiii, 921p] - Thieme, Darius L. (International Library of African Music, 2017)
pages: 111-117
Keywords: African Music